Constructing The Legal Safeguard For China’s Carbon Taxation - Deng, Haifeng; Wang, Anna (Journal of Sustainable Development Law and Policy, 2025)
Environmental protection practices of developed countries prove carbon taxation is an effective tool to reduce greenhouse effect, and China has already put it into official agenda. Based on Chinese environmental law system, the enforcement of carbon tax mainly faces four key challenges, contradiction with the existing taxes items; conflict with carbon trade system; adjustment of carbon tax collection and administrative structure; and coordination with international trade rules. In order to solve those problems, it is high time to build a legal protection system for carbon taxation. The essence of the legal protection system includes at least three aspects: Firstly, adjusting the existing environment tax rates. Secondly, coordinating with carbon trade system and make tax reduction policy for enterprises which have achieved reduction goals. Thirdly, constructing a dynamic balance administrative system and a comprehensive database system for carbon taxation.